Existence of Solutions of Nonlinear Stochastic Volterra Fredholm Integral Equations of Mixed Type - K. Balachandran; J.-H. Kim (International Journal of Mathematics and Mathematical Sciences)
We establish sufficient conditions for the existence and uniqueness of random solutions of nonlinear Volterra-Fredholm stochastic integral equations of mixed type by using admissibility theory and fixed point theorems. The results obtained in this paper generalize the results of several papers.